Kvinderne fra Lublin. Bevogtningspersonalet i Majdanek - Bundgård Christensen, Claus (Historisk Tidsskrift, 2013)
The Women from Lublin: The Guards of MajdanekResearch on the ordinary, lower level staff of concentration camps is sparse, especially as regards female guards, the so-called Aufseherinnen. The present study is based on unique source material stemming from the Majdanek concentration and extermination camp on the outskirts of Lublin in Poland. Its archive, which was transferred to the state archives in Moscow shortly after the camp’s liberation, contains what is probably the most comprehensive material on female guards from any of the German concentration camps. This is the first study to deal specifically with the women guards at Majdanek.Thirty women were employed as guards at Majdanek between October 1942 and April 1944. They had a number of duties, the most important of which was the so-called internal surveillance of the women inmates. This small number of guards meant that the camp was seriously understaffed, and the period from 1943 to 1944 was characterized by constant requests by various commanders for an increase in staff. For the most part, these requests were denied on grounds of personnel shortage and because Auschwitz along with the large women’s camp at Ravensbrück had first priority. Despite the small number of guards the camp was successful in averting riots and major attempts to escape, because external surveillance, in the hands of the SS, was extensive, while prisoner selfmanagement also played an important role. The small number of guards was not a phenomenon peculiar to Majdanek, but a tendency characteristic of the entire camp system.There were several ways in which a woman could find employment as a guard, but most of the guards at Majdanek had volunteered. In connection with the post-war trials, the last of which took place in 1981, the accused often claimed that they had been more or less coerced to take the job pursuant to the decree on service duty. It is true that this prescription was used from the first half of 1944 to recruit personnel, but it had little significance with regard to the personnel at Majdanek. It is shown that, by far, most of the guards had been hired before the ordinance was put to use.The training period for the guards varied from a few weeks to several months, but most of them had taken the longest period of about three-months’ time. The women, unlike their male counterparts, were not enrolled in the SS, but none the less subordinated to it as SS-Gefolge; and like the SS-male guards the women guards were under the jurisdiction of the SS-Sondergerichtbarkeit. There were disciplinary problems with the guard personnel at Majdanek, but sanctions for the women were relatively mild. Between October 1942 and December 1943 ten women had been penalized. Only a single person among them had been brought before the SS Police Court, where she was sentenced to three months in prison for theft. The others had been given milder penalties by their commandant for breach of discipline and standing orders. According to the autobiographical notes of Rudolf Höss, the camp commander at Auschwitz, the tendency at Majdanek to eschew harsh penalties was also true of other camps. The main reason for this was a serious shortage of personnel, which also had an impact on the women’s chances of resigning from service. The Majdanek archives contain a number of such denied requests. But like the SS guards the women were transferred about within the system, and most of them did duty at several camps.The archives can only indirectly throw light on the women’s share in the crimes against the prisoners, but it can be shown that most of the guards in question were on active duty in the camp while the gas chambers were running as well as in November 1943 in connection with the mass shooting during the so-called Aktion Erntefest. It is known with certainty that several guards assisted in the action, just as there are also known instances of taking part in the selection of victims. It can be clearly ascertained that the women guards at Majdanek were an integral part of the camp’s crimes of genocide. The degree to which each of them took part in the offensives varied, the recollections of survivors converge to a high degree on two particular guards who can only be designated as “Exzess-Täter.”A comprehensive sociological study of the women guards has never been undertaken, but it is possible to point out a number of common traits of the personnel at Majdanek. For the most part the women were in their twenties. Most were single, while a few were married and had children. All of them were German citizens. An important common trait was that none had skilled training or any education beyond a short period of elementary schooling. Most came from relatively poor conditions, making them heavily dependent on their wages, a circumstance useful to camp authorities and of which they were quite attentive. The guards were state employees with relatively high remuneration and a number of fringe benefits such as uniforms, room and board. Moreover, they could increase their pay through various types of bonus. It is difficult to derive any clear notions about their ideological motivation, but none of the women seem to have been party members or active in Nazi organizations. On the whole, a picture emerges of quite ordinary women, comparable to the results found in Christopher Browning’s study of the personnel of Reserve Police Battalion 101.There are probably several reasons why the guards at Majdanek took part in the abuse and killing of prisoners. Most of them began duty there before 1943 and arrived with experience, for instance, from Ravensbrück or Auschwitz. The fact that the women had spent a long time in the camp system is no doubt a significant factor in explaining their crimes; they adapted to an institutional framework that was conducive to assault and brutalized its personnel.Translated by Michael Wolfe